2013
DOI: 10.1186/1475-2840-12-156
|View full text |Cite
|
Sign up to set email alerts
|

Type 1 diabetes and cardiovascular disease

Abstract: The presence of cardiovascular disease (CVD) in Type 1 diabetes largely impairs life expectancy. Hyperglycemia leading to an increase in oxidative stress is considered to be the key pathophysiological factor of both micro- and macrovascular complications. In Type 1 diabetes, the presence of coronary calcifications is also related to coronary artery disease. Cardiac autonomic neuropathy, which significantly impairs myocardial function and blood flow, also enhances cardiac abnormalities. Also hypoglycemic episod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
47
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(55 citation statements)
references
References 114 publications
(162 reference statements)
2
47
0
Order By: Relevance
“…However, in select patients, it occurs in youth early in the course of the disease ( 15 ). CAN is linked to mortality risk, as shown by a metaanalysis of 15 diff erent studies ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in select patients, it occurs in youth early in the course of the disease ( 15 ). CAN is linked to mortality risk, as shown by a metaanalysis of 15 diff erent studies ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…Th is, in conjunction with reduced blood fl ow to nerve fi bers, contributes to the disorder ( 1 ). Myocardial blood fl ow activity in response to sympathetic stimulation is signifi cantly impaired after longstanding type 1 DM and may contribute to the eventual development of myocardial injury ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…Patients with T1D have a 2-4 times greater risk of developing atherosclerosis compared to people without diabetes mellitus, and cardiovascular events account for up to 44% of the total mortality in these patients (2,(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…It was revealed that cardiovascular disease occurs in a higher rate and at a younger age among patients with T1D when compared to normal people [5]. The risk of atherosclerosis is 2 -4 times higher in T1D patients compared to people without T1D [6] [7]. The only direct correlation between T1D and cardiovascular diseases is dyslipidemia, which is the elevation of lipids e.g., triglycerides cholesterol and/or fat phospholipids in the blood [8].…”
Section: Introductionmentioning
confidence: 99%
“…The only direct correlation between T1D and cardiovascular diseases is dyslipidemia, which is the elevation of lipids e.g., triglycerides cholesterol and/or fat phospholipids in the blood [8]. The presence of dyslipidemia (DLP) significantly increases cardiovascular risk among patient with T1D [6]. Diabetic dyslipidemia is defined as low levels of high-density lipoprotein cholesterol (HDL-C) and increased low-density lipoprotein cholesterol (LDL-C) and triglycerides (TGs) [9].…”
Section: Introductionmentioning
confidence: 99%